(3HgLI GdMGhjs - (3YeQ Hf eXaQ Hf YeQ H eMeO GHf CHj GdahGQS, CHh MaU, Rjf GdOjf GHf GdhQOj GdeYQj GdcfOj,J (B749 (3g` s; (3GdbRhjfj , fLe GdOjf YHO GdZaGQ Hf YHO GdcjQe GdbRhjfj,J (B665 (3g` s
(3ChdgG (B:s
(3hHYO aGdYde YXje GdefRdI aCHOC efg HGdCge hPdc Gdabg efg cGdMGhj aj GdLeY hGdEjLGR hGdaJGhj s
(3BNQgG (B:s
(3jfJgj HfgGjI YJb Ce GdhdO s
(3GdfSNI HgG MhGTs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3JHUQI GdYfhGf (B:s
(3fXes
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3Gdabg GdTGaYjs